Об изоморфизме регулярных NM-графов - Шулинок, Г.А. (Теорія оптимальних рішень, 2005)
Regular natural modular graphs with arbitrary number of generatices are considered. The first classification of regular NM-graphs is made. For NM-graphs with two generatrices an isomorphizm problem is solved completely. The paper tries to enumerate isomorphic regular NM-graphs.